Hydrogeographical characteristics of the Pragersko ponds - Vovk Korže, Ana (Journal for Geography, 2018)
The abstract presents The ponds Pragersko with an emphasis on the measured physical and chemical water properties. We performed the measurements because of the lack of these sort of results and because the Municipality of Slovenska Bistrica is collecting ideas about further development of this area. Hydrogeographical properties of water bodies are an important source of information for planning out everything that we could possible design on anthropological ponds in the future. Our goal was to collect the data on the field from November 2017 to May 2018 using measuring procedures and compare them to standard values. Due to the clay soil matrix, water can also clean itself. Which is why we didn’t detect any greater fluctuations, but water charachteristics still occur because of different seasons and activities by the ponds.